Pengaruh Pendidikan Kewirausahaan, Locus of Control, dan Media Sosial Terhadap Minat Berwirausaha: Pada Siswa Kelas XI SMK Negeri 2 Singaraja - Ni Putu Yunika Dewi; Made Ary Meitriana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
This study aims to determine the influence of entrepreneurship education, locus of control, and social media on entrepreneurial interest in grade XI students of SMK Negeri 2 Singaraja. The research method in this study is a quantitative research method with primary data obtained from questionnaire data measured using the Likert scale. The population of this study is grade XI students at SMK Negeri 2 Singaraja. The sample technique used is the proportionate stratified random sampling technique. The analysis technique used is multiple linear regression analysis with partial (t-test) and simultaneous (f-test) hypothesis tests. The results of this study show that (1). Entrepreneurship education has a positive and significant effect on students' interest in entrepreneurship which is shown by calculating the variables of entrepreneurship education of 9.717 > table 1.970 significance level 0.000 < 0.05, (2). The locus of control has a positive and significant effect on students' interest in entrepreneurship which is shown by the calculation of the entrepreneurship education variable of 14,898 > 1,970 table of significance level 0.000 < 0.05, (3). Social media has a positive and significant effect on students' interest in entrepreneurship which is shown by calculating the variables of entrepreneurship education of 15,530 > table 1,970 significance level 0.000 < 0.05, and (4). Entrepreneurship education, locus of control, and social media have a positive and significant effect on students' interest in entrepreneurship which is shown by the calculation of the variables of entrepreneurship education of 127.169 > Ftable 2.64 significance level 0.000 < 0.05.